A study to correlate histopathological findings in patients with abnormal uterine bleeding - Shukla, Mansi; Fonseca, Michelle N.; Kharat, Deepali; Tekale, Pallavi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Abnormal uterine bleeding (AUB) is a common gynecological problem associated with considerable morbidity and significantly affects the patients. The aim of the study was to analyze the histopathological patterns of endometrium in patients presenting with AUB and also to determine the incidence of AUB in various age groups. Methods: This is a retrospective study, conducted in the Department of Obstetrics and Gynaecology, in a tertiary care teaching hospital, Mumbai, India from March 2016 till date. All cases of AUB were included in the study. Data was entered in microsoft excel and managed in statistical package for the social sciences (SPSS) version 16. Analysis was done in the form of percentages and proportions and represented as tables where necessary. Results: A total of 120 cases were analyzed. Patients’ age ranged from 22-79 years. AUB was most common among the perimenopausal females (41-50years). The most common presenting symptom was heavy menstrual bleeding (53%). Dilatation and curettage (D&C) was performed in all cases and 96 underwent hysterectomy as final resort. Endometrial proliferative pattern was the most common histopathological finding and was seen in 27% patients, followed by endometrial hyperplasia in 13.5% patients, secretory endometrium (12.7%) and disordered proliferative endometrium were seen in 10.9% patients each. Malignancy was detected in 1.7% of cases and endometrial carcinoma was the most common lesion. Conclusions: Endometrial sampling is especially indicated in women above the age of 35 years to rule out malignancy and preneoplasia. Among the females with no organic pathology, normal physiological patterns with proliferative, secretory, and menstrual changes were observed. The most common endometrial pathology in this study was endometrial proliferation.